Broadband ESD protection circuits in CMOS technology. - Galal, S. (IEEE Journal of solid state circuits)
A broadband technique using monolithic T-coils is applied to electrostatic discharge (ESD) structures for both input and output pads. Fabricated in 0.18-μm CMOS technology, the prototypes achieve operation at 10 Gb/s while providing a return loss of -20 dB at 10 GHz. The human-body model tolerance is 1000 V for the input structure and 800-900 V for the output structure.